2006
DOI: 10.1063/1.2184308
|View full text |Cite
|
Sign up to set email alerts
|

CO adsorption and CO and O coadsorption on Rh(111) studied by reflection absorption infrared spectroscopy and density functional theory

Abstract: The adsorption of carbon monoxide on Rh(111) and on oxygen modified Rh(111) was investigated using thermal desorption spectroscopy, reflection absorption infrared spectroscopy (RAIRS), and density functional theory. The results show that CO adsorbs on Rh(111) in on top sites at low coverages. With increasing coverage hollow sites and bridge sites get occupied according to the RAIRS results. A new vibrational feature at high wave numbers was found in the on top region of the CO stretching frequency. This featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
88
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 59 publications
20
88
2
Order By: Relevance
“…Coadsorption of oxygen and CO on a Rh(111) surface also leads to a shift of the CO-Rh atop peaks to higher wavenumbers. 33,[36][37][38] The activity reported in Fig. 3b is similar under oxidative or reductive flux so that we rule out the presence of rhodium oxide proposed in ref.…”
Section: 28supporting
confidence: 74%
“…Coadsorption of oxygen and CO on a Rh(111) surface also leads to a shift of the CO-Rh atop peaks to higher wavenumbers. 33,[36][37][38] The activity reported in Fig. 3b is similar under oxidative or reductive flux so that we rule out the presence of rhodium oxide proposed in ref.…”
Section: 28supporting
confidence: 74%
“…Thus, CO oxidation, often quoted as a textbook example of catalytic reaction, is one of the best-known heterogeneous reactions and can be regarded as a benchmark system [1]. Though earlier studies have shown that some noble metals, such as Pd [2][3][4][5][6][7][8], Pt [3,[6][7][8][9][10][11][12][13], Rh [3,[6][7][8][9][14][15][16][17], and Au [18][19][20][21][22], can effectively catalyze CO oxidation, the high cost and high reaction temperature for efficient operations impose great limitations to the potential applications of these noble metal catalysts as good catalysts for CO oxidation. Therefore, it is understandable that scientists have been continuously endeavoring to seek suitable catalysts with high activity and lower cost to realize the low-temperature oxidation of CO.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a stronger binding strength between the adsorbates and the catalyst may promote associated product formation. [25][26][27][28] The binding strength can be described by the adsorption energy, E ad , which is defined as the energy difference between the adsorption system with the individual metallic surface and gas-phase molecules. To effectively convert CO to CO 2 at low temperatures, oxidation of CO on the late transition metals (especially the three-way catalysts composed of Rh, Pt, and Pd) is widely viewed as an effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…[14,24,[29][30] In addition to E ad , the energy barrier E b is another essential parameter to describe the rate of a reaction. Earlier attempts, both experimentally [23,25,[31][32][33][34] and theoretically, [25,[35][36][37][38][39] have been made to lower the E b values for CO oxidation on metallic surfaces. In contrast, recent studies address novel catalysts such as alloys, [40][41][42] clusters, [1,40,[43][44][45] and even metallic nanotubes.…”
Section: Introductionmentioning
confidence: 99%